Enhanced recovery after surgery programs improve short‐term outcomes after liver transplantation–A systematic review and meta‐analysis. Issue 11 (16th September 2021) - Tinguely, Pascale; Morare, Nolitha; Ramirez‐Del Val, Alejandro; Berenguer, Marina; Niemann, Claus U.; Pollok, Joerg M.; Raptis, Dimitri A.; Spiro, Michael
Abstract: This systematic review aimed to investigate the available quality of evidence (QOE) of enhanced recovery after surgery (ERAS) for liver transplantation (LT) on short‐term outcomes, grade recommendations, and identify relevant components for ERAS protocols. A systematic review and meta‐analysis were conducted on short‐term outcomes after LT when applying comprehensive ERAS protocols (> 1 ERAS component) versus control groups (CRD42021210374), following the GRADE approach for grading QOE and strength of recommendations. Endpoints were morbidity, mortality, length of stay, and readmission rates after ERAS for LT. Of 858 screened articles, two randomized controlled trials, two prospective, and one retrospective cohort studies were included (2002–2020). Frequent ERAS components were early extubation and postoperative antibiotic, fluid, and nutrition management. Overall complications were reduced in ERAS versus control cohorts (OR .4 (CI .2, .7), with no significant differences in mortality and hospital readmission rates. Intensive care unit and hospital length of stay were shorter in ERAS groups (percentage decrease, 55% and 29%, respectively). QOE for individual outcomes was rated moderate to low. ERAS protocols in LT are related to improved short‐term outcomes after LT (QOE; Moderate to low | Grade of Recommendation; Strong), but currently lack standardization.